2022
DOI: 10.3390/insects13030228
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Isoform-Specific Roles of FTZ-F1 in the Larval–Larval and Larval–Pupal Ecdyses in Henosepilachna vigintioctopunctata

Abstract: Fushi Tarazu Factor 1 (FTZ-F1), a member of the nuclear receptor superfamily, is the downstream factor of 20-hydroxyecdysone signaling. In Drosophila melanogaster, alternative transcription start and splicing in the FTZ-F1 gene generate αFTZ-F1 and βFTZ-F1 isoforms, which are vital for pair-rule segmentation in early embryogenesis and post-embryonic development, respectively. However, whether the same mRNA isoforms are present and exert the conservative roles remains to be clarified in other insects. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In the present study, we observed that knockdown of Hvcyp18a1 upregulated the expression of the 20‐hydroxyecdysone (20E) receptor gene ( HvEcR ), as well as four 20E response transcripts ( HvE75, HvHR3, HvBrC , and HvαFTZ‐F1 ), in H. vigintioctopunctata . Previous studies have identified these transcripts as 20E response genes in H. vigintioctopunctata (Wu et al, 2021; Wu, Chen, et al, 2022; Wu, Cheng, et al, 2022), Based on our findings, it can be inferred that CYP18A1 potentially plays a role in 20E elimination. Knockdown of Hvcyp18a1 represses the inactivation of 20E during the end of prepupal stage, resulting in elevated levels of 20E response transcripts compared to the control group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, we observed that knockdown of Hvcyp18a1 upregulated the expression of the 20‐hydroxyecdysone (20E) receptor gene ( HvEcR ), as well as four 20E response transcripts ( HvE75, HvHR3, HvBrC , and HvαFTZ‐F1 ), in H. vigintioctopunctata . Previous studies have identified these transcripts as 20E response genes in H. vigintioctopunctata (Wu et al, 2021; Wu, Chen, et al, 2022; Wu, Cheng, et al, 2022), Based on our findings, it can be inferred that CYP18A1 potentially plays a role in 20E elimination. Knockdown of Hvcyp18a1 represses the inactivation of 20E during the end of prepupal stage, resulting in elevated levels of 20E response transcripts compared to the control group.…”
Section: Discussionsupporting
confidence: 71%
“…Upon analyzing the RNAi phenotypes of Hvcyp18a1, we observed a striking resemblance to those observed in HvβFTZ-F1 knockdown beetles (Wu, Cheng, et al, 2022). Similar to HvβFTZ-F1 RNAi animals, the larvae depleted of Hvcyp18a1 developed normally until the prepupal stage but displayed pupation defects in H. vigintioctopunctata.…”
Section: Cyp18a1 Deficiency Inhibits Transcription and Release Of βFt...mentioning
confidence: 61%
“…The H. vigintioctopunctata beetles were reared using fresh potato foliage at the vegetative growth or young tuber stages [ 43 , 44 ]. At this feeding protocol, the ladybirds progressed through four distinct larval instars (3, 2, 2 and 3 days, respectively), prepupal (2 days), pupal (4 days) and adult stages.…”
Section: Methodsmentioning
confidence: 99%
“…The eggplant lady beetle ( Henosepilachna vigintioctopunctata ), a defoliating pest attacking Solanaceae and Cucurbitaceae crops in many Asian countries [ 42 ], only has four instars. Disruption of the 20E signal fails to bring about supernumerary instars or second pupae in H. vigintioctopunctata [ 43 , 44 ]. We accordingly hypothesized that the larval instars in the beetle were fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Two isoforms of Ftz‐f1 have been described in dipterans like D. melanogaster (Lavorgna et al, 1993) and A. aegypti (Cruz et al, 2009), as well as in some coleopterans and lepidopterans (Wu et al, 2022). However, a single ftz‐f1 has been identified in the genome of the cockroach B. germanica (Harrison et al, 2018), which plays critical functions during the last nymphal moults (Cruz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%